2020
DOI: 10.1029/2020wr027197
|View full text |Cite
|
Sign up to set email alerts
|

A Semianalytical Method to Fast Delineate Seawater‐Freshwater Interface in Two‐Dimensional Heterogeneous Coastal Aquifers

Abstract: The freshwater-seawater interface is one of the most important regions in coastal aquifer systems, delineating the subsurface into zones with distinct fluid density and biogeochemical properties. Heterogeneity in hydraulic conductivity is inherent to geological formations, resulting in distinct interface profiles. Currently available analytical solutions are limited to homogeneous and stratified aquifers, and numerical simulations of variable-density flow and transport are the only option to characterize the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…In the upscaling procedure, we used a simple mean and did not consider hydraulic conductivity in the diagonal direction. This problem has been pointed out by Rathore et al (2020), who found that the geometric mean underestimates the seawater intrusion extent on average. Using a full hydraulic conductivity tensor may preserve more detailed heterogeneity (Li et al, 2011;Zhang et al, 2006).…”
Section: Model Simplificationsmentioning
confidence: 95%
See 1 more Smart Citation
“…In the upscaling procedure, we used a simple mean and did not consider hydraulic conductivity in the diagonal direction. This problem has been pointed out by Rathore et al (2020), who found that the geometric mean underestimates the seawater intrusion extent on average. Using a full hydraulic conductivity tensor may preserve more detailed heterogeneity (Li et al, 2011;Zhang et al, 2006).…”
Section: Model Simplificationsmentioning
confidence: 95%
“…We know that all aquifers are heterogeneous, and incorporating any heterogeneity, either as layers or more complex systems, strongly influences both the salinity distribution and position of the freshwater‐saltwater mixing zones and therefore large‐scale density‐driven SGD. Previous studies have evaluated the impacts of heterogeneity on SGD by numerical simulations of groundwater flow through continuous random fields (e.g., multi‐Gaussian distributions) of K (De Vriendt et al., 2020; Geng & Michael, 2020; Held et al., 2005; Kerrou & Renard, 2010; Rathore et al., 2020). The results showed stronger effects on saline SGD than fresh SGD.…”
Section: Introductionmentioning
confidence: 99%
“…This assumption is reasonable for the rainfall intensity in a small area, but it is not realistic for the recharge of aquifers, because the process of infiltration is affected by geological characteristics such as topography, soil type and evapotranspiration, land use type, and human activities (Park et al., 2014; Werner et al., 2017). Field investigations have showed that the groundwater lens shape and thickness can be affected by spatially variable recharge rates induced by ridge topography (Ruppel et al., 2000), terrain and vegetation patterns (Schneider & Kruse, 2003, 2006), distribution of different soil types (Park et al., 2014) and heterogeneous hydrogeological properties including hydraulic conductivity, impermeable layer, and boundary conditions (Cellone et al., 2018; Holt et al., 2019; Rathore et al., 2018; Rathore, Lu & Luo, 2020; Sheng et al., 2020). In addition, the knowledge and insights on how the volume and shape of a groundwater lens change in response to spatially variable recharge rates can provide very useful information for determining the location and recharge rate of artificial recharge to control seawater intrusion (Bouwer, 2002; Rajasekhar et al., 2019; Senanayake et al., 2016).…”
Section: Introductionmentioning
confidence: 99%